PEMBUATAN TILEMAP DAN PATHFINDING BERTIPE STAGGERED MAP PADA GAME ENGINE COCOS2D-X UNTUK GAME BERFORMAT REAL TIME STRATEGY - , ASWINDA PRIMA PUTRA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Game is one of the most favorite entertainment media for many people. Rapid growth of game industry has positive effect on the development of game engine to develop a game. One of the most populer game engine is cocos2d-x. In development of RTS game there are many aspect as the concern including tilemap and pathfinding. Kind of suitable tilemap type for RTS genre game is staggered map, therefore on the development of the pathfinding algorithm for games also have to obey the rule of staggered map. In this research will discuss about making tilemap and pathfinding class on cocos2d-x game engine. Analysis conducted on the coordinates on staggered map, so can be implemented on tilemap class for tile placement and pathfinding class to determine neighbors of a tile in the implementation of A* algorithm. The test results indicate that tilemap and pathfinding class can be implemented in simple real time strategy game using cocos2d-x game engine.